Emotion regulation from early adolescence to emerging adulthood and middle adulthood: Age differences, gender differences, and emotion-specific developmental variations - Zimmermann, Peter; Iwanski, Alexandra (International journal of behavioral development, 2014)
Despite the growing research on emotion regulation, the empirical evidence for normative age-related emotion regulation patterns is rather divergent. From a life-span perspective, normative age changes in emotion regulation may be more salient applying the same methodological approach on a broad age range examining both growth and decline during development. In addition, emotion-specific developmental patterns might show differential developmental trends. The present study examined age differences in seven emotion regulation strategies from early adolescence (age 11) to middle adulthood (age 50) for the three emotions of sadness, fear, and anger. The results showed specific developmental changes in the use of emotion regulation strategies for each of the three emotions. In addition, results suggest age-specific increases and decreases in many emotion regulation strategies, with a general trend to increasing adaptive emotion regulation. Specifically, middle adolescence shows the smallest emotion regulation strategy repertoire. Gender differences appeared for most emotion regulation strategies. The findings suggest that the development of emotion regulation should be studied in an emotion-specific manner, as a perspective solely on general emotion regulation either under- or overestimates existing emotion-specific developmental changes.